OZIQ - OVQAT SANOATI KORXONALARI FAOLIYATINI BOSHQARISH VA RIVOJLANISH MEXANIZMINI TAKOMILLASHTIRISH (Marketing Journal, 2026)
AbstractThe article examines the issues of improving the management and developmentmechanisms of food industry enterprises. The study analyzes the current state ofenterprise management systems, factors affecting production and financialperformance, and mechanisms for shaping development strategies. Special attention isgiven to the implementation of innovative approaches, digital technologies, and theactivation of investment processes to ensure sustainable development of food industryenterprises. The findings are of practical significance for enhancing management processes, increasing competitiveness, and defining long-term development prospectsof the sector.Keywords: control mechanism, influencing factors, reforms, food industry,exports, imports, food exports.